PERANCANGAN KAWASAN SENI TARI DAN SENI TEATER DI KOTA SURABAYA - Hasbi Romadhon; Retno Hastijanti (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
Modern art is growing rapidly in Surabaya. A number of dance studios concentrate on developing a combination of traditional and modern arts. However, there are quite a few dance groups that develop and modify modern creations, for example Marlupi Dance, Gito Maran. Efforts to create artistic life in Surabaya were initiated by the Surabaya Arts Council (DKS) as well as theater, painting and music associations. Exhibitions of painting and theater arts are often held at the Youth Hall Building. Meanwhile, traditional dance performances are always held at the People's Entertainment Park (THR) and Cultural Park. The Surabaya Symphony Orchestra (SSO) also plays an important role in growing the art of music in Surabaya